Assessing the Structural Characteristics of the Japanese Version of the Adult Social Care Outcomes Toolkit for Carers. Issue 1 (February 2022) - Nakamura-Thomas, Hiromi; Yamaguchi, Mai; Yamaguchi, Ikushi; Rand, Stacey
Due to the absence of standardized Quality of Life (QoL) measures for informal family caregivers of recipients of long-term care (LTC) in Japan, translation and cross-cultural adapted LTC outcome measures are needed for research and evaluation. In this study, we assessed the validity and reliability of the factor structure and response system of the translated and cross-culturally adapted Japanese version of the Adult Social Care Outcomes Toolkit for Carer (J-ASCOT-Carer). Participants were 872 informal family caregivers of adults who lived at home and required LTC services. Almost half (46%) of the participants were between 50 and 59 years old, 85% were employed, and 69% resided with their care recipients. We used the combined factor analysis and item response theory approach. Model fit indices included factor loading, path coefficients, root mean square error of approximation, standardized root mean square residual, and comparative fit index. This study confirmed the one factor structure that was identified in the original English version of the ASCOT-Carer. The values for the model fit indices indicated a good fit. Moreover, the validity and reliability of the response system were confirmed. Therefore, the J-ASCOT-Carer is a reliable assessment instrument to measure QoL of Japanese caregivers of adults requiring LTC.